Uncovering Core–Periphery Dynamics: Pakistan’s Global Stance and Scope of the China-Pakistan Economic Corridor - Zahid Khan; Shi Guoqing (China Quarterly of International Strategic Studies, 2023)
This research delves into core–periphery dynamics in Pakistan’s relations with the United States and China, with a focus on the China-Pakistan Economic Corridor (CPEC). It investigates how these dynamics shape interactions and Pakistan’s global stance. The study analyzes the Pakistan-U.S. relationship, where the U.S. core dominance influences Pakistan’s socioeconomic trajectory. Shifting to the Pakistan-China partnership, China’s dual core–semi-periphery roles define its involvement in CPEC, merging developmental investments with strategic interests. This study employs a comparative analysis to dissect the core–periphery dynamics within Pakistan’s interactions with the United States and China, specifically in the case of CPEC. Correspondingly, the core–periphery framework exposes structural imbalances and the interplay of power, economics, and geopolitics. The research highlights the framework’s insights — revealing traditional core–periphery dynamics in Pakistan-U.S. ties and intricate complexity in Pakistan-China relations. China’s multifaceted role as a developmental supporter and strategic actor adds layers to the narrative. In essence, the core–periphery framework unveils the interwoven narratives of power, economic reliance, and strategic motivations that underpin the evolving global order.